Efficacy and Safety of Daptomycin versus Vancomycin for Bacteremia Caused by Methicillin-Resistant Staphylococcus aureus with Vancomycin Minimum Inhibitory Concentration > 1 µg/mL: A Systematic Review and Meta-Analysis - Masaru Samura; Yuki Kitahiro; Sho Tashiro; Hiromu Moriyama; Yuna Hamamura; Isamu Takahata; Rina Kawabe; Yuki Enoki; Kazuaki Taguchi; Yoshio Takesue; Kazuaki Matsumoto (MDPI AG, 2022)
This systematic review and meta-analysis compares the efficacy of daptomycin and vancomycin in adult patients with bacteremia by methicillin-resistant Staphylococcus aureus (MRSA) with vancomycin minimum inhibitory concentration (MIC) > 1 µg/mL. We searched the PubMed, Web of Science, Cochrane Library, and ClinicalTrials.gov databases on 12 May 2020. All-cause mortality (primary outcome) and treatment success rates were compared and subgroups stratified by infection source risk level and method of vancomycin susceptibility testing were also analyzed. Seven studies (n = 907 patients) were included in this efficacy analysis. Compared with vancomycin, daptomycin treatment was associated with significantly lower mortality (six studies, odds ratio (OR) 0.53, 95% confidence interval (CI) 0.29-0.98) and higher treatment success (six studies, OR 2.20, 95% CI 1.63-2.96), which was consistent regardless of the vancomycin MIC test method used. For intermediate-risk sources, daptomycin was a factor increasing treatment success compared with vancomycin (OR 4.40, 95% CI 2.06-9.40), and it exhibited a trend toward a higher treatment success rate for high-risk sources. In conclusion, daptomycin should be considered for the treatment of bacteremia caused by MRSA with vancomycin MIC > 1 µg/mL, especially in patients with intermediate- and high-risk bacteremia sources.